Neurological Wilson’s Disease in Adolescents: A Case Series from South India: Neurological Wilson’s Disease in Adolescents - Jose, Priya; Rajan, Nishanth; Kumar Kommu, Peter Prasanth; Krishnan, Guruvishagan; Thirugnanasamban, Kavinamalar vaithiyanathan (International Clinical Neuroscience Journal, 2026)
Wilson’s disease is an autosomal recessive disorder that disrupts copper metabolism, leading to serious consequences in the liver and brain, including cirrhosis and the characteristic Kayser-Fleischer (KF) ring in the cornea. Our study focuses on children who presented with neurological symptoms, with or without hepatic involvement. While there have been a few reports from northern India, data on pediatric cases in southern India are sparse, highlighting the need for more comprehensive research in this region. In this series, we report on nine adolescent children diagnosed with neurological manifestations of Wilson’s disease who presented to a tertiary care center. We collected relevant clinical histories, along with details from physical and neurological examinations, from the medical record system. This comprehensive data collection aimed to provide a clearer understanding of the clinical presentation and progression of neurological Wilson's disease in our patient cohort. Wilson’s disease should be considered as one of the initial differential diagnoses even when there is only one neurological manifestation and without hepatic involvement in adolescents as well.